Pre-catch and discard mortality in Northeast Atlantic herring and mackerel fisheries: consequences for stock estimates and advice. (9th August 2021) - Tenningen, Maria; Zimmermann, Fabian; Enberg, Katja
Abstract: Unaccounted mortality caused by discarding or pre-catch losses is a major challenge for fisheries management. In pelagic fisheries, a considerable proportion of catches may be lost due to intentional release of unwanted catch (slipping) or net bursts (fishing net tears due to the weight of the catch). Here we review and estimate ranges of discard and pre-catch mortality for two important pelagic fisheries, the Northeast Atlantic (NEA) mackerel and Norwegian spring spawning (NSS) herring, and explore the effects on stock estimates and catch advice. We show that mortality caused by discarding, slipping, and net bursts is unknown but probably corresponds to a considerable percentage of total registered catches. Including estimated unaccounted mortality into assessment models leads to underestimation of the stock levels by 3.7–19.5% and 2.8–6.8% for NEA mackerel and NSS herring, respectively, corresponding to up to several million tonnes of fish that die annually due to fishing without being landed. If discard and pre-catch mortality were eliminated, allowed catches could increase by 10–20%. We demonstrate that unaccounted mortality in pelagic fisheries may be substantial, affecting stock estimates and catch advice. This may undermine the sustainable management and efficient use of pelagic resources.